2012
DOI: 10.4025/actascianimsci.v34i3.13327
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gastrointestinal indices in Nile tilapia fed with different diets

Abstract: The adequate diet of Nile tilapia in their growth early stages is fundamental to the success of culture subsequent stages. The goal of the present work was to evaluate the Nile tilapia growth fed with different diets, and to morphometrically characterized the gastrointestinal tract of this species. The treatments consisted of three diets: (D 1 ) natural food, (D 2 ), commercial feed and (D 3 ) commercial feed + natural food. In the qualitative phytoplankton analysis, there was greater representation of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The increase in EI in the BF system can be directly related to the consumption of substrates, which results in an increase in the surface of the intestine, enabling greater contact and, consequently, greater absorption of nutrients (Moreira et al, 2012). These same authors observed an increase in this parameter when fish were fed diets containing natural feed, compared to diets based on feed.…”
Section: Discussionmentioning
confidence: 89%
“…The increase in EI in the BF system can be directly related to the consumption of substrates, which results in an increase in the surface of the intestine, enabling greater contact and, consequently, greater absorption of nutrients (Moreira et al, 2012). These same authors observed an increase in this parameter when fish were fed diets containing natural feed, compared to diets based on feed.…”
Section: Discussionmentioning
confidence: 89%
“…In the fertilized treatment, two additional organic fertilizer applications (18 kg of organic fertilizer each) were performed, one in late October and the other in early December. Fertilization occurred only in the initial months of production, as fish consume more plankton in the early stages, as reported by Moreira et al (2012). According to Mo et al (2014), fish feces and the remains of uneaten feed help to fertilize the ponds.…”
Section: Study Area and Managementmentioning
confidence: 89%
“…The total rearing time for the larvae was 14 days at salinities of 5-7 ppt. In Nile tilapia fish fry provided with artificial feed, phytoplankton, and zooplankton, at least 13% of the content in their stomachs was zooplankton [12], ranging from 8-13% [13].…”
Section: Discussionmentioning
confidence: 99%
“…Rotifer feeding over 4 days at a salinity of 5-7 ppt resulted in a survival rate of 92.4% within 4 days, while for 2 days it was 81.75%, compared to 81.0% for the control. [12] reared Nile tilapia O. niloticus fish larvae from the larval stage for 100 days and obtained survival rates of approximately 25% (with natural feed) and 80-90% (with artificial feed and a combination of natural and artificial feed). [14] provided rotifers to mud crab zoea Scylla olivacea larvae three times a day, resulting in survival rates of 58% on the third day and 22% on the fourth day, which were higher than those from feeding once or twice.…”
Section: Discussionmentioning
confidence: 99%